Fungal keratitis: study of increasing trend and common determinants - Acharya, Yogesh; Acharya, Bhawana; Karki, Priyanka (Nepal Journal of Epidemiology, 2017)
Fungal keratitis is one of the leading cause of ocular morbidity. Fungal keratitis possesses a clinical challenge due to its slow pathologic process, overlapping features, diagnostic difficulty, and potential complications. Its increasing trend can be attributed to the use of contact lens, non-judiciary corticosteroid, and vegetative trauma. Early diagnosis and treatment is the cornerstone for its effective control. Knowledge of pathological course and clinical characteristics of fungal keratitis will definitely add in early diagnosis and treatment, with reduction in ocular morbidity. This review article explores the risk factor of fungal keratitis, its clinical course and management strategy.